Combustion wave of metalized extruded double-base propellants. (1st February 2019) - Elbasuney, Sherif; Fahd, Ahmed
Abstract: Aluminum metal fuel, with combustion heat of 32, 000 J/g, is of interest as high energy density material. Aluminum is able to react not only with free oxygen but also with inert combustion gaseous products. This study reports on the impact of ultrafine aluminum particles on combustion characteristics of double-base propellant. Metalized double-base propellant formulations were developed by solventless extrusion process. Combustion characteristics were evaluated using small-scale ballistic evaluation test motor. There was an increase in average operating pressure, burning rate, and characteristic exhaust velocity C∗ with aluminum content. Even though there was no oxidizer available for aluminum oxidation; aluminum alone offered 7.6% increase in average operating pressure, 24.6% increase in burning rate, 7.8% increase in C∗. The main outcome of this study is that this superior performance was achieved at 4 wt% solid loading level. Aluminum particles could alter the combustion wave by increasing the combustion flame temperature, average operating pressure inside the combustion chamber, thermal conductivity of DB propellant. All these combustion criteria could decrease the thickness of the dark zone, allowing the luminous flame to be more adjacent to the burning surface; therefore the reaction could proceed faster. Even though the developed metalized DB formulations were found to be more energetic with an increase in calorific value by 4.6%; they demonstrated good thermal behavior to reference formulation using DSC. These findings confirmed that aluminum is an outstanding energetic ingredient for solid rocket propulsion. It has unique ability to react with inert gases generating substantial heat output.